2014
DOI: 10.1088/1758-5082/6/2/025008
|View full text |Cite
|
Sign up to set email alerts
|

A three-dimensional cell-laden microfluidic chip for in vitro drug metabolism detection

Abstract: Three-dimensional tissue platforms are rapidly becoming the method of choice for quantification of the heterogeneity of cell populations for many diagnostic and drug therapy applications. Microfluidic sensors and the integration of sensors with microfluidic systems are often described as miniature versions of their macro-scale counterparts. This technology presents unique advantages for handling costly and difficult-to-obtain samples and reagents as a typical system requires between 100 nL to 10 µL of working … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 55 publications
0
17
0
Order By: Relevance
“…Although 3D printed microfluidic devices containing cell-laden hydrogels have been developed by a number of groups [15,16,21], this study marks a first demonstration of a 3D printed device capable of culturing multicellular spheroids. Microfluidic perfusion culture of multicellular spheroids often necessitates the presence of micro-structures (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although 3D printed microfluidic devices containing cell-laden hydrogels have been developed by a number of groups [15,16,21], this study marks a first demonstration of a 3D printed device capable of culturing multicellular spheroids. Microfluidic perfusion culture of multicellular spheroids often necessitates the presence of micro-structures (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…However, the development of 3D printed microfluidic devices for organs-on-chip applications remains relatively under-explored. To date, a number of studies have already demonstrated the successful implementation of 3D printed microfluidic devices coupled with bioprinted [14][15][16][17][18][19][20] or photopatterned cell-laden hydrogels [21]. While this approach can recreate a 3D environment by supporting cells with synthetic or natural extracellular matrices and provide a means to probe cell-matrix interactions, it is limited in recapitulating multicellular interactions and organization, which is highly relevant to physiologically cell-dense tissues, such as tumors and hepatic tissues.…”
Section: Introductionmentioning
confidence: 99%
“… 66 , 67 ). Such methodology can be applied to deposit cells with multi-nozzle deposition systems over channels built by a digital micro-mirror technique 68 . Integration of multi-head bioprinting with a maskless solid-freeform fabrication system was also developed, which speeded up the fabrication process and eliminated toxic chemicals.…”
Section: Integration Of Bioprinting With Microfluidicsmentioning
confidence: 99%
“…Moreover, initial prototyping may require multiple iterations and lithographic mold fabrication can be prohibitively expensive ($150-$500 per design from 3 rd party manufacturers). Other investigators have 3D printed microfluidic cell culture models 29,30 , but these single channel devices do not integrate membranes for recapitulating tissue-tissue interfaces. Therefore, in this study, we aimed to fabricate multi-layered, membrane integrated organs-on-chips without PDMS soft lithography.…”
mentioning
confidence: 99%